Thermo-viscoplastic behavior of 304 austenitic stainless steel at various strain rates and temperatures: Testing, modeling and validation. (15th March 2020) - Jia, B.; Rusinek, A.; Pesci, R.; Bahi, S.; Bernier, R.
Highlights: New experimental set-up developed for dynamic tests at low and high temperatures. Deformation behavior of 304 ASS at high strain rates for a large range of temperatures. Constitutive relations considering martensitic transformation. Experiments and numerical simulations of the material behavior under ballistic impact tests at low and high temperatures. Abstract: This paper presents a systematic study of the thermo-viscoplastic behavior of a 304 austenitic stainless steel (ASS). The experiments were conducted over a wide range of strain rates (10 −3 s −1 to 3270 s −1 ) and temperatures (-163°C to 172°C), for which the deformation behavior of 304 ASS becomes more complex due to the strain-induced martensitic transformation (SIMT) effect. Dynamic tests at low/elevated temperatures were conducted using the Hopkinson technique coupled with a cooling device/heating furnace, and temperature distribution within the specimen was verified to be uniform. Experimental results showed that the strain hardening rate of 304 ASS was strongly affected by SIMT effect. For quasi-static tests (10 −3 s −1 to 1 s −1 ) at low temperatures (-163°C to -20°C), the stress-strain relations exhibited an S-shape and a second strain hardening phenomenon. The strain rate sensitivity and temperature sensitivity of 304 ASS were also different from metallic materials deformed by dislocation glide. Several unexpected phenomena including the negative strain rate sensitivity and the changing temperature sensitivity from quasi-static to dynamic tests were observed. Based on experimental results, an extension of the Rusinek-Klepaczko (RK) model considering SIMT effect was used to simulate the deformation behavior of 304 ASS: it predicted flow stress curves of 304 ASS above -60°C correctly. In addition, to validate the extended RK model and the identified model parameters, numerical simulations of ballistic impact tests of 304 ASS plates at various temperatures were carried out, showing a good agreement with experiments. Graphical abstract: Image, graphical abstract